Benchmarking of techniques used to assess the freeze damage in potatoes. (December 2019) - Jha, Piyush Kumar; Vidot, Kevin; Xanthakis, Epameinondas; Falourd, Xavier; Fontaine, Joran; Jury, Vanessa; Le-Bail, Alain
Abstract: In this study, benchmarking of methods used for assessing freeze damage in potatoes was carried out. Initially, the samples were frozen by subjecting them to three different temperatures (i.e. at – 18 °C, − 30 °C, and at − 74 °C). Then, different analytical techniques comprising of focused methods (i.e. cryo-Scanning elctron microscopy-cryo-SEM, confocal laser scanning microscopy-CLSM) and global methods (i.e. texture analysis, low field nuclear magnetic resonance (NMR), exudate loss and colour change) were used to assess the impact of the freezing treatment from the different point of view addressed by each method. As a result, each of these methods were able to distinguish significantly fresh samples from the frozen-thawed samples. Focused methods like cryo-SEM and CLSM methods could differentiate the impact of all three different protocols. Meanwhile, texture analysis (including conventional method and novel method based on a touchless laser puff firmness tester), NMR and exudate loss could only determine the quality difference between − 18 °C and − 74 °C freezing conditions. Colour analysis was found as an inappropriate parameter for comparing the three freezing protocols. Among all analytical techniques, cryo-SEM provides the most authentic information about the product as the analysis is performed in frozen state, while for other techniques the product is thawed prior to analysis. Highlights: Benchmarking of methods for accessing freeze damage in potatoes was carried out. Three different freezing protocols have been compared. Focused methods could differentiate the impact of all different freezing protocols. Texture, NMR and exudate loss had limitations to differentiate freezing conditions.